Community empowerment and environmental stewardship in sustainable tourism: The role of ecotourism - Affifah, Aida Nur (Ecotourism and Environment Conservation, 2025)
Background: Ecotourism is a form of sustainable tourism development. Nglanggeran Tourism Village is one of the sustainable self-sustaining tourism villages that applies ecotourism principles in managing its tourism. Findings: The Nglanggeran Tourism Village was pioneered since 2007 by local youths and community leaders which started with anxiety towards people who were not responsible for exploiting natural resources, so that a desire arose to maintain, manage and develop the existing potential so that these limited resources would continue to exist and can be enjoyed by generations. Methods: This research is a descriptive qualitative research with data collection techniques in the form of interviews, observation, and documentation conducted in Nglanggeran Tourism Village, Patuk District, Gunungkidul. Conclusion: The results of the study show that the strategies listed in Gunungkidul District Regulation No. 3 of 2014 concerning the Gunungkidul Regency Regional Tourism Master Plan for 2014- 2025 with steps to increase the competitiveness of tourism products, increase tourism business partnerships, and fulfill environmental and socio-cultural responsibilities that have been carried out properly. Natural potential, the existence of a harmonious community, preservation of ancestral traditions, strategic location and proximity to markets, as well as the return of the natural and village tourism trend are driving factors, while the emergence of parties that do not match the vision of development, the mindset of people who cannot seizing opportunities, the minimal role of BUMDes, the difficulty of controlling tourists who do not understand the concept of ecotourism, and weak tourism development planning schemes are the inhibiting factors for sustainable tourism development in Nglanggeran Tourism Village to date. Novelty/Originality of this article: A sustainable tourism development strategy based on ecotourism principles fosters environmental conservation, local community empowerment, and responsible tourism practices to ensure long-term ecological and socio-economic benefits.